Experiências de leitura em tempos e espaços adversos : um olhar sobre o universo de um grupo de meninas em medidas socioeducativas - Kegler, Nelcy Teresinha da Rosa (2022)
Literary reading, in addition to the numerous aspects known in the field of formal education, can lead subjects to re-signify their lives, giving them a new direction, a new look at their fears, feelings, uncertainties, as well as enabling them to dive into their own world in order to better understand their emotions. The general objective of this thesis is to identify how reading experiences make it possible to change the subjectivity of adolescents in compliance with socio educational measures in non-formal reading spaces. As specific objectives were listed: i) to develop reading experiences and/or literary interventions with subjects in non-formal or non institutionalized reading spaces; ii) to know the perceptions of the reality of the world of female subjects from literary texts worked on in reading meetings; iii) understand how the different reading experiences can be factors to expand subjectivity, as well as the possibility of (re)construction as subjects; iv) sensitize subjects to the experience of reading as a promoter of well-being, expansion of knowledge and fruition. The theoretical framework was based on studies by Larrosa (2003, 2019) on issues of reading experiences; by Petit (2010, 2013, 2017, 2019) in the study of reading in adverse spaces; and Candido (1989, 2004) on reading as a human right; in addition to other authors. As for the methodological basis, the study is a qualitative research, of the action-research type, carried out with a group of seven adolescents aged between 13 and 19 years, female, who were in compliance with socio-educational measures at the Centro de Specialized Reference for Social Assistance (CREAS), in the city of Chapecó/SC. Data collection took place at the end of the second half of 2019 and in March and April 2020, with some iterations for completion in 2021 (due to the SARS-CoV-2 pandemic). Data collection took place through a questionnaire, with open and closed questions, allowing to map the profile of the participants. The main conclusions of the first stage of the study were: i) the adolescents showed a predominance of a female family figure in relation to the mediation of reading in their childhood; ii) showed, however, low motivation and few experiences of interaction with reading, although some demonstrated to have memories of contact with stories and books in childhood; iii) the school had little participation as a motivating environment for reading.In the second stage, there was interaction through literary texts with different approaches chosen by the group around the theme "Woman", combined with different genres The interaction with literary texts presented significant elements, as there was the insertion of the Public Library space, which provided access to hitherto unknown cultural assets (collections), which broadened the horizons of cultural references. The research made it possible to identify a significant change in attitude among the participants, leading them to feel like they really are – young people like any other – with dreams, wishes and their way of being at this stage of life. The importance of the role of the mediator in the process and also of the library as a space for inclusion and cultural democratization is highlighted. Although the research took place partially during a pandemic, it brought relevant contributions to the literary field, considering reading as a source of awareness of the role and full rights of all citizens, and literary art and other manifestations as a space that allows multiple possibilities of reframing life, opposing the adversities of the world.